Advances in the Evolutionary Understanding of MHC Polymorphism. Issue 4 (April 2020) - Radwan, Jacek; Babik, Wiesław; Kaufman, Jim; Lenz, Tobias L.; Winternitz, Jamie
Abstract : Proteins encoded by the classical major histocompatibility complex ( MHC ) genes incite the vertebrate adaptive immune response by presenting peptide antigens on the cell surface. Here, we review mechanisms explaining landmark features of these genes: extreme polymorphism, excess of nonsynonymous changes in peptide-binding domains, and long gene genealogies. Recent studies provide evidence that these features may arise due to pathogens evolving ways to evade immune response guided by the locally common MHC alleles. However, complexities of selection on MHC genes are simultaneously being revealed that need to be incorporated into existing theory. These include pathogen-driven selection for antigen-binding breadth and expansion of the MHC gene family, associated autoimmunity trade-offs, hitchhiking of deleterious mutations linked to the MHC, geographic subdivision, and adaptive introgression. Highlights: Novel MHC alleles have been demonstrated to confer better resistance to local parasites. MHC alleles may differ by orders of magnitude in the range of antigens they bind. Promiscuous alleles and species with more MHC genes appear to be more common in pathogen-rich populations. The number of MHC class I alleles correlates negatively with the size of the T cell receptor repertoire, supporting the role of constraints associated with increasing ranges of bound antigens. Deleterious mutations accumulate around MHC genes and likely affect the evolutionary dynamics of MHC haplotypes.